Karakteristik Enkapsulat Teh Instan Daun Kenikir (Cosmos caudatus Kunth.) pada Perlakuan Penambahan Emulsifier Tween 80 - Cahyana, Emita Dwi; Wrasiati, Luh Putu; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
The aims of research were to know the effect of addition emulsifier tween 80 on the making of Cosmos caudatus Kunth. instant tea, and to determine the addition of the best tween 80 emulsifier to the Cosmos caudatus Kunth. instant tea . This research used a simple randomized block design, wich the concentration of tween 80 as the factor. The concentration of tween 80 used in this research are 0%, 0.5%, 1%, 1.5%, 2%, 2.5%. The data obtained were analyzed by analysis of variance and then processed by the Tukey test. The results showed that the concentration of tween 80 influenced the yield, solubility, total flavonoids, brightness level, redness level, yellowish level, and texture organoleptic tests which included stickiness, dryness and smoothness. The best treatment based on physicochemistry was obtained by adding 1% concentration of tween 80 , with a yield value at 11.08 %, solubility at 96.77%, total flavonoids at  9.1041 mg QE/g, the level of brightness (L*) at 36.49, the level of redness (a*) at 19.36, and the level of yellowish (b*) at 30.63. Based on the results of the organoleptic test, respondendts chose treatment without the addition of tween 80, with a stickiness texture value at 4.20 (not sticky), , dryness at 4.60 (dry) , and smoothness at 4.75 (smooth) . Keywords : Cosmos caudatus Kunth. leaves, instant tea, encapsulation, tween 80